The Effect of Silymarin on Telomerase Activity in the Human Leukemia Cell Line K562 - Faezizadeh, Zohreh; Mesbah-Namin, Seyed Ali Reza; Allameh, Abdolamir (Planta Medica, 2012)
Telomerase has been proposed as a novel and potentially selective target in cancer therapy. Silymarin, which is a standardized mixture of flavonolignans from the medical plant Silybum marianum, has potent effects against various types of cancer cells, but its effect on telomerase activity in the human leukemia cell line K562 has not been investigated. The aim of this study was to examine the mechanism of silymarin-induced apoptosis in K562 cells, with particular emphasis on its effect on telomerase activity. The antiproliferation effect of silymarin on K562 cells was evaluated by the MTT assay. To measure apoptosis, Hoechst 33342 staining and flow cytometry were used. The telomerase activity was determined using the telomeric repeat amplification protocol (TRAP)-ELISA assay. The treatment of the K562 cells with silymarin resulted in a significant inhibition of cell growth and telomerase activity. Also, a positive correlation was found between telomerase inhibition and induction of apoptosis in silymarin-treated K562 cells. These results suggest a novel mechanism in the anticancer activity of silymarin in human leukemia K562 cells and may provide a basis for future development of anti-telomerase therapies.
Keywords: K562; silymarin; telomerase activity; apoptosis; Silybum marianum; Asteraceae